Cinnamon oil downregulates virulence genes of poultry respiratory bacterial agents and revealed significant bacterial inhibition: An in vitro perspective - Ahmed Mohammed Erfan; Sherif Marouf (Veterinary World, 2019)
Background and Aim: Respiratory bacterial agents represent one of the most harmful factors that ordinarily threaten the poultry industry and usually lead to great economic losses. Meanwhile, there is a global demand to avoid the highly emerging antibiotic resistance and antibiotic residues in edible meat. Whereas, the use of alternatives became of great priority, especially for those substances extracted from natural plant origin. The study aimed to evaluate the antibacterial effect of cinnamon oil as a herbal extract on different respiratory bacterial agents.